Auditoría de cumplimiento y su relación con las obligaciones fiscales tributarias de la empresa Exp. E Imp. Manobal C. Ltda., cantón Quevedo, período 2012 - Cedillo Saltos, Tania Alexandra (2015)
This research is based on the Compliance Audit and their relation to taxation tax obligations Exp. E Imp. Manobal C. Ltda., Quevedo Canton, period 2012. For the execution of this work has raised the following formulation How the problem affects Compliance Audit and its relationship with the tax obligations of the company tax Exp. E Imp. Manobal C. Ltda. Quevedo Canton, period 2012? the same is duly justified, recognizing their internal control weaknesses with the application of the questionnaire, seeking to detect, assess and correct flaws in it, using techniques or tools Compliance Audit to contribute to the administration adequate decision making , the same that will be transformed into opportunities. General Objective: To audit such compliance and their relation to taxation tax obligations Exp. E Imp. Manobal C. Ltda., Quevedo Canton, period 2012, it should be noted that the methodology used for this study was the interview and questionnaire tools that allowed analyzing the different independent variables, and the results showed the research can be defined that the process of internal control of the accounting department to meet tax tax obligations that keeps the company is well defined, it was determined on the results of internal control a confidence level of 77.54% (High) and a level of 22.46% Risk (Low) the compliance with them on the scheduled dates it guarantees, despite the same urgency that cause differences especially in the transactional Annex. The accounting records and supports the company are conducted in accordance with the laws meet the regulatory requirements of the tax administration determines the level of compliance to tax tax obligations is high, the accounting department is kept informed of the reforms and updates tax through training and external consultants with whom the company has. Therefore the recommendations and conclusions to the administration was structured.